Comparison of neuroimaging by CT and MRI and correlation with neurological presentation in eclampsia - Jindal, Megha A.; Gaikwad, Harsha S.; Hasija, Bhagat D.; Vani, Kavita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: The objective of the study was to compare computed tomography (CT) and magnetic resonance imaging (MRI) findings of eclampsia patients with respect to neurological signs and symptoms. Methods: This is a prospective observational study, 25 patients of eclampsia were studied, statistical analysis was done by Fishers’ exact and chi square test. Results: All patients in our study presented with antepartum or intrapartum eclampsia with neurological features ranging from headache, altered consciousness to coma. On neuroimaging by MR transiently high T2 signal intensity in the cerebral cortex and sub cortical white matter was seen, including edema. With MR angiography generalized vasospasm was also seen in 40% cases. MRI was found to be co-relating more than CT with the neurological presentation and had 90% sensitivity and 100% sensitivity. Conclusions: Symptoms like visual blurring, loss of vision and ophthalmological signs in eclampsia suggest occipital lobe involvement. Magnetic resonance imaging abnormalities in eclampsia correlate well with clinical findings as compared to CT and can be better imaging modality in eclampsia patients.